Daya Saing dan Determinan Penawaran Ekspor Kopi Indonesia ke Jepang - Fikri Aldi Dwi Putro; Lovina Aresta Putri; Gunawan Prawira (Jurnal Agribisnis Indonesia, 2024)
Indonesian coffee export has reached various countries, and one of its destinations is Japan. Moreover, Indonesia and Japan have begun to normalize their bilateral trade through the Indonesia-Japan Economic Partnership Agreement (IJEPA). However, the average Indonesian coffee export to Japan shows a downturn which is expected due to low competitiveness and utilization of IJEPA. This research aims to examine the competitiveness and its effect towards Indonesian coffee export to Japan in the long and short term and employs multiple linear regression using the Error Correction Mechanism (ECM) approach. The research result shows that Indonesian coffee has a medium comparative advantage in the Japanese market with downturn growth during the 2001–2022 period. The regression results suggest that the economic distance significantly affects Indonesian coffee exports in the short term. Furthermore, the other factors that affect Indonesian coffee exports in the long term are Japan’s real GDP, Japan’s inflation rate, and IJEPA implementation.